Effects of vitamin D on apoptosis and betatrophin in the kidney tissue of experimental diabetic rats - Demircan, Selçuk; Onalan, Erhan; Kuloğlu, Tuncay; Aydın, Süleyman; Yalçın, Mehmet Hanifi; Gözel, Nevzat; Dönder, Emir (Acta Biomedica Atenei Parmensis, 2020)
The aim of this study is to investigate the effects of vitD on betatrophin and apoptosis in rat kidney tissue using an experimental diabetes model created with STZ. 41 male Wistar-albino breed rat were assigned to 5 groups, which included 3 groups consisting of 7 animals each and 2 groups consisting of 10 animals each. The control group received no treatments. Single-dose 0.1 M sodium buffer was administered ip to the Buffer group. The VitD group was orally administered 200 IU/day vitD.The Diabetes group was injected ip with single-dose 50 mg/kg STZ by dissolving the material in 0.1 M sodium buffer. Subjects with a glucose level exceeding 250 mg/dl were accepted to be diabetic. The Diabetes + VitD group was injected ip with 50 mg/kg single-dose STZ by dissolving the material in 0.1 M sodium buffer. Once diabetes was established, 200 IU/day vitamin D was administered orally. The histological and biochemical analyses of the Control, Buffer, and Vitamin D groups revealed similar serum TOS and TAS levels, and TUNEL positivity and betatrophin immunoreactivity. While the Diabetes group showed significantly higher TOS levels and TUNEL positivity compared to the Control group, their TAS levels and betatrophin immunoreactivity were significantly reduced. The Diabetes+Vitamin group demonstrated significantly lower TOS levels and TUNEL positivity compared to the Diabetic group, and their TAS levels and betatrophin immunoreactivity increased significantly.In conclusion; experimental diabetes was found to increase TOS and apoptotic cells and decrease TAS and betatrophin levels in kidney tissue in experimental diabetes, and that administering VitD as treatment caused a decrease in TOS and apoptotic cells and an increase in TAS and betatrophin levels. It was concluded that future studies needed to investigate various experimental diabetes times so that the role of diabetes in the pathophysiology of its effect on kidney tissue could be uncovered.